Impact of Temporal and Spatial Resolution in Slope-Plant-Atmosphere Interaction Modelling - Maryam Sadat Maddah Sadatieh; Aikaterini Tsiampousi; Athanasios Paschalis (Geotechnical and Geological Engineering, 2026)
Soil–Plant-Atmosphere Interaction (SPAI) is an essential factor in slope behaviour, affecting water inflow and outflow, and thereby influencing Pore Water Pressures (PWP), soil strength and stiffness, and slope stability and serviceability. Due to its complexity, SPAI and its effect on slope behaviour are best described by hydro-mechanically coupled numerical analysis, rendering the boundary conditions (BC) used to replicate atmospheric conditions critical. Here, different considerations have been made regarding the temporal and spatial variation of these BCs to assess their effect on slope behaviour. Specifically, daily and monthly atmospheric data were contrasted, dynamic vegetation growth was juxtaposed with static vegetation, and water extraction with depth due to transpiration was compared with a simplified approach where evapotranspiration was modelled to occur from the ground surface. A representative cut slope was considered, and fully coupled hydro-mechanical analyses were conducted under different BCs to study its stability and serviceability. The numerical results highlight which modelling choices significantly influence predicted performance, particularly under climate change, and which can be safely simplified. Guidance is provided for balancing computational efficiency with accuracy in geotechnical design.

An Integrated Modelling Framework to Determine Terrestrial Carbon Dioxide Removal via Enhanced Rock Weathering - Ziyan Zhang; Gregory Jones; Salvatore Calabrese; Matteo Bertagni; Simone Fatichi; Bonnie Waring; Athanasios Paschalis (Global Change Biology, 2025)
Enhanced rock weathering (ERW) is an emerging carbon dioxide removal (CDR) strategy that can support net‐zero emission targets. However, current ERW modelling efforts rely on assumptions that introduce substantial variation in CDR estimates across varying ecosystems and hydroclimatic conditions. They typically ignore or oversimplify plant–soil interactions and high‐frequency hydrological dynamics, obscuring short‐term weathering responses and biotic feedbacks to soil moisture dynamics. Here, we introduce an integrated, process‐based modelling framework, T&C‐SMEW, which represents ecohydrological and ERW dynamics, along with microbially explicit biogeochemical processes. We compared framework simulations against a controlled mesocosm experiment and long‐term field observations, demonstrating its ability to reproduce feedstock cation release, soil pH dynamics, gross primary production, and CO 2 fluxes. T&C‐SMEW reveals hydrological constraints and vegetation effects on ERW‐mediated CDR by quantifying impacts on ecosystem respiration, net ecosystem exchange, and alkalinity export, emphasising the importance of ecohydrological modelling for ecosystem‐level CDR estimation. These advances provide a modelling framework for identifying optimal deployment scenarios to establish ERW as a viable and operationally feasible CDR approach.

Numerical study of the effect of soil-plant-atmosphere interaction under future climate projections and different vegetation covers - Maryam Sadat Maddah Sadatieh; Aikaterini Tsiampousi; Athanasios Paschalis (Geomechanics for Energy and the Environment, 2025)

Microscale to neighbourhood scale: Impact of shading on urban climate - Christopher Wilson; Jonathan K.P. Shonk; Sylvia I. Bohnenstengel; Athanasios Paschalis; Maarten van Reeuwijk (Building and Environment, 2025)

When do plant hydraulics matter in terrestrial biosphere modelling? - Athanasios Paschalis; Martin G. De Kauwe; Manon Sabot; Simone Fatichi (Global Change Biology, 2024)
The ascent of water from the soil to the leaves of vascular plants, described by the study of plant hydraulics, regulates ecosystem responses to environmental forcing and recovery from stress periods. Several approaches to model plant hydraulics have been proposed. In this study, we introduce four different versions of plant hydraulics representations in the terrestrial biosphere model T&C to understand the significance of plant hydraulics to ecosystem functioning. We tested representations of plant hydraulics, investigating plant water capacitance, and long‐term xylem damages following drought. The four models we tested were a combination of representations including or neglecting capacitance and including or neglecting xylem damage legacies. Using the models at six case studies spanning semiarid to tropical ecosystems, we quantify how plant xylem flow, plant water storage and long‐term xylem damage can modulate overall water and carbon dynamics across multiple time scales. We show that as drought develops, models with plant hydraulics predict a slower onset of plant water stress, and a diurnal variability of water and carbon fluxes closer to observations. Plant water storage was found to be particularly important for the diurnal dynamics of water and carbon fluxes, with models that include plant water capacitance yielding better results. Models including permanent damage to conducting plant tissues show an additional significant drought legacy effect, limiting plant productivity during the recovery phase following major droughts. However, when considering ecosystem responses to the observed climate variability, plant hydraulic modules alone cannot significantly improve the overall model performance, even though they reproduce more realistic water and carbon dynamics. This opens new avenues for model development, explicitly linking plant hydraulics with additional ecosystem processes, such as plant phenology and improved carbon allocation algorithms.

Hydrometallurgical recovery of silver and gold from waste printed circuit boards and treatment of the wastewater in a biofilm reactor: An integrated pilot application - Dimitrios Vlasopoulos; Panagiota Mendrinou; Paschalis Oustadakis; Pavlina Kousi; Athanasios Stergiou; Spyridon-Dionysios Karamoutsos; Artin Hatzikioseyian; Petros E. Tsakiridis; Emmanouella Remoundaki; Styliani Agatzini-Leonardou (Journal of Environmental Management, 2023)

Rainfall manipulation experiments as simulated by terrestrial biosphere models: Where do we stand? - Athanasios Paschalis; Simone Fatichi; Jakob Zscheischler; Philippe Ciais; Michael Bahn; Lena Boysen; Jinfeng Chang; Martin De Kauwe; Marc Estiarte; Daniel Goll; Paul J. Hanson; Anna B. Harper; et al. (Global Change Biology, 2020)
Changes in rainfall amounts and patterns have been observed and are expected to continue in the near future with potentially significant ecological and societal consequences. Modelling vegetation responses to changes in rainfall is thus crucial to project water and carbon cycles in the future. In this study, we present the results of a new model‐data intercomparison project, where we tested the ability of 10 terrestrial biosphere models to reproduce the observed sensitivity of ecosystem productivity to rainfall changes at 10 sites across the globe, in nine of which, rainfall exclusion and/or irrigation experiments had been performed. The key results are as follows: (a) Inter‐model variation is generally large and model agreement varies with timescales. In severely water‐limited sites, models only agree on the interannual variability of evapotranspiration and to a smaller extent on gross primary productivity. In more mesic sites, model agreement for both water and carbon fluxes is typically higher on fine (daily–monthly) timescales and reduces on longer (seasonal–annual) scales. (b) Models on average overestimate the relationship between ecosystem productivity and mean rainfall amounts across sites (in space) and have a low capacity in reproducing the temporal (interannual) sensitivity of vegetation productivity to annual rainfall at a given site, even though observation uncertainty is comparable to inter‐model variability. (c) Most models reproduced the sign of the observed patterns in productivity changes in rainfall manipulation experiments but had a low capacity in reproducing the observed magnitude of productivity changes. Models better reproduced the observed productivity responses due to rainfall exclusion than addition. (d) All models attribute ecosystem productivity changes to the intensity of vegetation stress and peak leaf area, whereas the impact of the change in growing season length is negligible. The relative contribution of the peak leaf area and vegetation stress intensity was highly variable among models.

Activin, neutrophils, and inflammation: just coincidence? - Paschalis Sideras; Eirini Apostolou; Athanasios Stavropoulos; Alexandros Sountoulidis; Arianna Gavriil; Anastasia Apostolidou; Evangelos Andreakos (Seminars in Immunopathology, 2013)

The effects of muscle damage on walking biomechanics are speed-dependent - Themistoklis Tsatalas; Giannis Giakas; Giannis Spyropoulos; Vassilis Paschalis; Michalis G. Nikolaidis; Dimitrios E. Tsaopoulos; Anastasios A. Theodorou; Athanasios Z. Jamurtas; Yiannis Koutedakis (European Journal of Applied Physiology, 2010)

Comparison between leg and arm eccentric exercises of the same relative intensity on indices of muscle damage - Athanasios Z. Jamurtas; V. Theocharis; T. Tofas; A. Tsiokanos; C. Yfanti; V. Paschalis; Y. Koutedakis; K. Nosaka (European Journal of Applied Physiology, 2005)